Surgathon: a new model for creating a surgical innovation ecosystem in low-resource settings. Issue 2 (16th February 2020) - Mitra, Shivani; Ashby, Joanna; Muhumuza, Arsen; Ndayishimiye, Isaac; Wasserman, Isaac; Santhirapala, Vatshalan; Peters, Alexander W; Vervoort, Dominique; Jacob, Oshin; Gnanaraj, Jesudian; Ganesh, Praveen; Afshar, Salim
Abstract : Innovation ecosystems and emerging technologies can potentially accelerate the access to safe, affordable surgical care in low-resource settings. There is a need to develop localised innovation ecosystems that can establish an initial culture and catalyse the creation, adoption and diffusion of innovation. The surgathon model outlines one approach to seeding surgical innovation ecosystems. International academic institutions collaborated on six global surgery, innovation and ethics-themed hackathons ('surgathons') across India and Rwanda between 2016 and 2019. Over 1598 local multidisciplinary students participated, learning about challenges in the delivery of surgical care and ideating solutions that could leverage appropriate technology and resources for impact. Pursuing student ideas and evaluating their implementation past the surgathons continues to be an active effort. Surgathons have unfolded in different permutations based on local faculty, institution and health system context. The surgathon model is a novel method of priority setting challenges in global surgery and utilises locally driven expertise and innovation capacity to derive ethical solutions. The model offers a path for low-resource setting students and faculty to learn, advocate and innovate for improved surgical care.